Perancangan aplikasi untuk peramalan penjualan dan perencanaan pembelian persediaan ayam potong - Dewi, Agnes Nanda Puspita; Daryanto, Yosef (Jurnal Teknik Industri dan Manajemen Rekayasa, 2024)
Many web-based applications have been developed to help business activities. Web-based applications can be accessed from computers or mobile phones with various specifications and memory capacities, making it easier for many users. In this research, a web-based application was developed to assist in forecasting and planning activities for purchasing broiler chickens to be sold by a small business. Forecasting and purchase planning for broiler chickens were carried out to overcome shortages and excess supplies caused by fluctuating demand and the absence of sales recording and evaluation. Forecasting is carried out using the FB Prophet method which has the smallest error. Purchase calculation takes into account weight loss and losses due to dead chickens. The design starts with designing the user interface, creating source code, testing, and deploying the program. The application was built with Visual Studio Code with the Python programming language, Flask micro-framework, and XAMPP localhost. The web-based application that has been created helps owners and workers determine purchase amounts and show previous historical data. This application helps make planning easier and more accurate.